Copper coordination modulates prion conversion and infectivity in mammalian prion proteins. Issue 1 (31st December 2023) - Legname, Giuseppe
ABSTRACT: In mammals the cellular form of the prion protein (PrP C ) is a ubiquitous protein involved in many relevant functions in the central nervous system. In addition to its physiological functions PrP C plays a central role in a group of invariably fatal neurodegenerative disorders collectively called prion diseases. In fact, the protein is a substrate in a process in which it converts into an infectious and pathological form denoted as prion. The protein has a unique primary structure where the unstructured N-terminal moiety possesses characteristic sequences wherein histidines are able to coordinate metal ions, in particular copper ions. These sequences are called octarepeats for their characteristic length. Moreover, a non-octarepeat fifth-copper binding site is present where copper coordination seems to control infectivity. In this review, I will argue that these sequences may play a significant role in modulating prion conversion and replication.